(untitled) (Journal of Pharmaceutical Negative Results, 2023)
E-learning plays an important role in the field of education in line with the changing technological advances. This method is a new method that follows the current learning trends in helping students explore knowledge without time limit. Accordingly, the introduction of e-modules using web applications have become a new method replacing conventional methods. There are many studies conducted in a variety of learning methods, but the overall impact related to the use of e-modules are still lacking. Therefore, this study aims to examine the impact of the use of e-modules in learning and facilitation. A systematic literature review was used to achieve the objectives of the study. The results of the study found that there are over 300 related articles and there are 20 highly relevant articles and published in from 2017 to 2020 from various databases. From the analysis and survey conducted, it was found that there is an influence from the use of e-modules in the learning process and facilitation. Among the profound effects that can be seen are through aspects of attitude, performance as well as stimulating active student involvement.